EKSEKUSI OBJEK JAMINAN FIDUSIA DALAM KONTRAK PEMBIAYAAN KONSUMEN DI KOTA PALU - Alfian, Alfian (Katalogis, 2017)
The problems of this research are the legal consequences of the execution of the collateral vehicles that do not yet have a Fiduciary certificate in consumer financing agreement in Palu and the roles of relevant agencies without going through the execution of fiduciary registration in consumer financing agreement in Palu. The objective of this research is to determine the legal consequences of the execution of the collateral vehicles that do not yet have a Fiduciary certificate in consumer financing agreement in Palu and the roles of relevant agencies without going through the execution of fiduciary registration in consumer financing agreement in Palu. This research uses empirical legal research that uses primary and secondary data then presented in the form of inductive thinking pattern -of specific to general things. The research concludes that the legal consequences of fiduciary execution that is not registered in terms of the debtor committedÂ torts so that the normatively, the creditors unauthorizedly use parate executie (direct execution), and the process of execution should be done by filing a civil lawsuit to the District Court through the process of the Civil Procedure Code until downs of judge's verdict that has permanent legal force. The execution which uses executorial title based on Fiduciary certificate, then the sale of collateral objects should be submissive and obedient to the Law of Civil Procedure. The role of the Ministry of Law and Human Rights in supervising fiduciary certificating is related to creditors' obligations of certifying fiduciary through the attribution of authority granted by the state under Article 12 UUJF.